Stimulating local public employment: Do general grants work? - Heléne Lundqvist; Matz Dahlberg; Eva Mörk (Institute for the Study of Labor (IZA), 2010)
The effectiveness of public funds in increasing public employment has long been a question on public and labor economists' minds. In most federal countries local governments employ large fractions of the working population, meaning that a tool for stimulating local public employment can substantially affect the overall unemployment level. This paper asks whether general grants to lower-level governments have the potential of doing so. Applying the regression kink design to the Swedish grant system, we are able to estimate causal effects of intergovernmental grants on personnel in different local government sectors. Our robust conclusion is that personnel in the central administration increased substantially after a marginal increase in grants, but that such an effect was lacking both for total personnel and personnel in child care, schools, elderly care, social welfare and in technical services. We suggest several potential reasons for these results, such as heterogeneous treatment effects and bureaucratic influence in the local decision-making process.
Keywords: C33; H11; H70; J45; 330; fiscal federalism; intergovernmental grants; public employment; regression kink design; instrumental variables; Finanzausgleich; Kommunalverwaltung; Öffentlicher Dienst; Beschäftigungseffekt; Schätzung; Schweden